Aortic valve replacement via a right parasternal approach in a patient with a history of coronary artery bypass surgery and pericardiectomy: a case report - Takuya Nakayama; Miki Asano (Surgical Case Reports)
Abstract Background The number of patients who require aortic valve replacement after coronary artery bypass grafting continues to increase. Re-operative cardiovascular surgery after coronary artery bypass grafting has various risk factors related to median re-sternotomy. It is particularly essential to avoid damage to the living graft. We successfully performed aortic valve replacement via right parasternal thoracotomy in a patient who had undergone coronary artery bypass grafting. Case presentation An 80-year-old man who had undergone coronary artery bypass grafting was referred to our hospital for syncope caused by severe aortic valve stenosis. He also had a history of pericardiotomy for constrictive pericarditis. His left internal thoracic artery bypass graft was patent. Aortic valve replacement was performed through a small right parasternal thoracotomy during cardiac arrest following cardiopulmonary bypass under moderate hypothermia and hyperkalemia by intermittent selective antegrade cardioplegia. His postoperative course was uneventful. Conclusion Aortic valve replacement via right parasternal thoracotomy with moderate hypothermia and hyperkalemia was safe and effective for avoidance of re-sternotomy-related complications.